Use of sponge iron as an indirect electron donor to provide ferrous iron for nitrate-dependent ferrous oxidation processes: Denitrification performance and mechanism. (August 2022) - Wang, Peng; Li, Wenxuan; Ren, Shuang; Peng, Yuzhuo; Wang, Yaning; Feng, Muyu; Guo, Kehuan; Xie, Huina; Li, Jie
Graphical abstract: Highlights: SI as an indirect electron donor can drive the NDFO process. Fe(OH)2 is the main electron donor in the SI–NDFO system. An average TN reduction rate of 0.42 mg–TN/(gVSS·h) were achieved. SI dosage, pH, temperature, and NO3 – –N concentration influenced NO3 – –N removal. SI contributes to the enrichment of Fe–oxidizing bacteria in activated sludge. Abstract: Sponge iron (SI) can serve as an indirect electron donor to provide Fe(II) for the nitrate-dependent ferrous oxidation (NDFO) process, producing OH – and magnetite. The SI–NDFO system mainly uses Fe(OH)2 as an electron donor, achieving a TN reduction rate of 0.42 mg–TN/(gVSS·h) for a period of at least 90 days. The enrichment of iron-oxidizing bacteria and the competition of iron-carbon micro-electrolysis for reaction sites on the surface of SI are the main reasons for the improvement of total nitrogen removal efficiency (TNRE). With an influent NO3 – –N concentration of 50 mg/L and a SI concentration of 50 g/L (at pH 5.0 and 30 °C), the TNRE reached a maximum level of 38.28%. In addition, reducing the pH environment was found to improve the denitrification efficiency of the SI–NDFO system, although denitrification stability was also reduced as a result. Overall, the SI-mediated NDFO process is a promising technique.